2019
DOI: 10.1097/cji.0000000000000289
|View full text |Cite
|
Sign up to set email alerts
|

Improving Immunotherapy Against B-Cell Malignancies Using γδ T-Cell–specific Stimulation and Therapeutic Monoclonal Antibodies

Abstract: Tumor antigen–targeting monoclonal antibodies (mAbs) are an important element of current cancer therapies. Some of these therapeutic mAbs enable antibody-dependent cell mediated cytotoxicity (ADCC) against tumor cells. However, cancer-related functional impairment of immune effector cells may limit the clinical efficacy of antibody treatments. We reckoned that combining mAbs with cell-based immunotherapies would provide a clinically relevant synergism and benefit for cancer patients. Here, we focus on γδ T cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…Therefore, the combination of clinically used therapeutic antibodies with adoptive Vδ2 T cell transfer might enhance the efficacy. 200 , 201 Further, γδ T cell activity is also regulated by checkpoint receptors. Vδ2T cells transiently upregulate PD-1 expression upon activation.…”
Section: Combination Matters: How To Improve γδ T Cell Therapymentioning
confidence: 99%
“…Therefore, the combination of clinically used therapeutic antibodies with adoptive Vδ2 T cell transfer might enhance the efficacy. 200 , 201 Further, γδ T cell activity is also regulated by checkpoint receptors. Vδ2T cells transiently upregulate PD-1 expression upon activation.…”
Section: Combination Matters: How To Improve γδ T Cell Therapymentioning
confidence: 99%
“…Hence, the recognition of BTN3A activated by phosphoantigens can elicit cytotoxic effector functions of Vγ9Vδ2 T cells. In addition, stimulation through phosphoantigens and Interleukin (IL)-2 can upregulate the expression of FcγRIII (CD16) in circulating Vδ2 T cells [65], which when combined with therapeutic antibodies such as Rituximab or Obinutzumab can enhance the antibody dependent cellular cytotoxicity (ADCC) of Vγ9Vδ2 T cells and enhance their lytic activity on cancer cells, especially in hematological indications [66,67] and Neuroblastoma [68]. In another study, activated Vγ9Vδ2 T cells bound to Trastuzumab-treated breast cancer cells via CD16 and thereby exerted ADCC.…”
Section: Cytotoxicitymentioning
confidence: 99%
“…The capability of Vγ9Vδ2 T cells to undergo massive clonal expansion in infection settings is being exploited ex vivo using direct or indirect BTN3A agonists BrHPP or amino-bisphosphonates (such as zoledronic acid) in combination with IL-2. Many in vitro expansion protocols for γδ T cells have been established, opening the door for large-scale experiments, pre-clinical models and adoptive transfer studies [67,97] (Table 1). In the context of cancer therapy, it is now possible to highly enrich autologous cells by ex vivo expansion and re-infuse them into a cancer patient.…”
Section: Adoptive T Cell-transfer and In Vivo Stimulationmentioning
confidence: 99%
“…Intriguingly, both ibrutinib and venetoclax induce a significant increase in the frequency of γδ T cells [27], which are cytotoxic cells that share several NK-cell features such as CD16 expression and ADCC. In a very recent report, Hoeres et al demonstrated that both T and NK cells contribute to GA101-induced ADCC in an elegant and interestingly basic study [28].…”
Section: Discussionmentioning
confidence: 99%